Optical characterization of bougainvillea glabra leaf extract for solar cell applications - Adekanmbi, Martins; Amaechi, Chukwuwendu Jeffrey (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study explores the potential of Bougain Villea (BV) leaf extract as a natural material in dye-sensitized solar cells (DSSCs). There has been a lot of attention paid to solar cells and other renewable energy sources in recent times due to their capacity to reduce dependency on fossil fuels and alleviate the consequences of climate change. The optical characteristics of the BV leaf extract were studied to determine its suitability for use in DSSCs. UV-Vis spectroscopy was used to measure the optical properties of the BV extract. Absorption spectra were found to be in the range of 420 - 900 nm. The optical band gap of the Bougain Vilea (M) and (AE) extract was determined to be 1.8 eV and 1.9 eV respectively. The results indicate that Bougain Vilea extract can be a potential natural material for DSSCs, as it is affordable and easily accessible. This study presents an in-depth analysis of the optical characteristics of Bougain Vilea extract and demonstrates its potential application in DSSCs. Further research is needed to optimize Bougain Vilea extract for use in DSSCs.